Interaction with Caveolin-1 Modulates G Protein Coupling of Mouse β(3)-Adrenoceptor - Sato, Masaaki (American Society for Biochemistry and Molecular Biology, 2012)
Caveolins act as scaffold proteins in multiprotein complexes and have been implicated in signaling by G protein-coupled receptors. Studies using knock-out mice suggest that β(3)-adrenoceptor (β(3)-AR) signaling is dependent on caveolin-1; however, it is not known whether caveolin-1 is associated with the β(3)-AR or solely with downstream signaling proteins. We have addressed this question by examining the impact of membrane rafts and caveolin-1 on the differential signaling of mouse β(3a)- and β(3b)-AR isoforms that diverge at the distal C terminus. Only the β(3b)-AR promotes pertussis toxin (PTX)-sensitive cAMP accumulation. When cells expressing the β(3a)-AR were treated with filipin III to disrupt membrane rafts or transfected with caveolin-1 siRNA, the cyclic AMP response to the β(3)-AR agonist CL316243 became PTX-sensitive, suggesting Gα(i/o) coupling. The β(3a)-AR C terminus, SP(384)PLNRF(389)DGY(392)EGARPF(398)PT, resembles a caveolin interaction motif. Mutant β(3a)-ARs (F389A/Y392A/F398A or P384S/F389A) promoted PTX-sensitive cAMP responses, and in situ proximity assays demonstrated an association between caveolin-1 and the wild type β(3a)-AR but not the mutant receptors. In membrane preparations, the β(3b)-AR activated Gα(o) and mediated PTX-sensitive cAMP responses, whereas the β(3a)-AR did not activate Gα(i/o) proteins. The endogenous β(3a)-AR displayed Gα(i/o) coupling in brown adipocytes from caveolin-1 knock-out mice or in wild type adipocytes treated with filipin III. Our studies indicate that interaction of the β(3a)-AR with caveolin inhibits coupling to Gα(i/o) proteins and suggest that signaling is modulated by a raft-enriched complex containing the β(3a)-AR, caveolin-1, Gα(s), and adenylyl cyclase.